Analisis Hubungan Tingkat Pendidikan Akhir Dan Kedisiplinan Terhadap Produktivitas Kerja Karyawan PT. Shin Hwa Biz - Safitri Rohmawati; Irawan; Yulaikah (GLOBAL SCIENTS PUBLISHER, 2025)
This research was conducted with the aim of knowing and testing the influence of educational and disciplinary variables partially and simultaneously on employee work productivity. The data analysis technique used in this research is quantitative. In this research, data collection was carried out by distributing questionnaires. The research population was 490 people and samples were taken using the Slovin formula so that the total sample was 83 respondents. Data analysis techniques use validation tests, reliability tests, classical assumption tests, multiple regression tests and hypothesis tests. The research results show that partially education has no influence on employee work productivity, while discipline has a positive and significant influence on employee work productivity. Simultaneously, education and discipline together have a significant effect on employee work productivity. The correlation between education and discipline has a very strong relationship with a value (R2) of 0.840, while the final ability of education and discipline is 84% ​​and the remaining 16% can be explained by other variables not studied.